Anthrax Toxin-Mediated Delivery In Vivo and In Vitro of a Cytotoxic T-Lymphocyte Epitope from Ovalbumin - Ballard, Jimmy D. (American Society for Microbiology, 1998)
We reported earlier that a nontoxic form of anthrax toxin was capable of delivering a cytotoxic T-lymphocyte (CTL) epitope in vivo, such that a specific CTL response was primed against the epitope. The epitope, of bacterial origin, was fused to an N-terminal fragment (LFn) from the lethal-factor component of the toxin, and the fusion protein was injected, together with the protective antigen (PA) component, into BALB/c mice. Here we report that PA plus LFn is capable of delivering a different epitope—OVA(257–264) from ovalbumin. Delivery was accomplished in a different mouse haplotype, H-2K(b) and occurred in vitro as well as in vivo. An OVA(257–264)-specific CTL clone, GA-4, recognized EL-4 cells treated in vitro with PA plus as little as 30 fmol of the LFn-OVA(257–264) fusion protein. PA mutants attenuated in toxin self-assembly or translocation were inactive, implying that the role of PA in epitope delivery is the same as that in toxin action. Also, we showed that OVA(257–264)-specific CTL could be induced to proliferate by incubation with splenocytes treated with PA plus LFn-OVA(257–264). These findings imply that PA-LFn may serve as a general delivery vehicle for CTL epitopes in vivo and as a safe, efficient tool for the ex vivo expansion of patient-derived CTL for use in adoptive immunotherapy.